HLA-DRB1*07:01–HLA-DQA1*02:01–HLA-DQB1*02:02 haplotype is associated with a high risk of asparaginase hypersensitivity in acute lymphoblastic leukemia - Nóra Kutszegi; Xiaoqing Yang; András Gézsi; Géza Schermann; Dániel J. Erdélyi; Ágnes F. Semsei; Krisztina M. Gábor; Judit C. Sági; Gábor T. Kovács; András Falus; Hongyun Zhang; Csaba Szalai (Haematologica, 2017)
Hypersensitivity reactions are the most frequent dose-limiting adverse reactions to Escherichia coli-derived asparaginase in pediatric acute lymphoblastic leukemia (ALL) patients. The aim of the present study was to identify associations between sequence-based Human Leukocyte Antigen Class II region alleles and asparaginase hypersensitivity in a Hungarian ALL population. Four-digit typing of HLA-DRB1 and HLA-DQB1 loci was performed in 359 pediatric ALL patients by using next-generation sequencing method. Based on genotypic data of the two loci, haplotype reconstruction was carried out. In order to investigate the possible role of the HLA-DQ complex, the HLA-DQA1 alleles were also inferred. Multivariate logistic regression analysis and a Bayesian network-based approach were applied to identify relevant genetic risk factors of asparaginase hypersensitivity. Patients with HLA-DRB1*07:01 and HLA-DQB1*02:02 alleles had significantly higher risk of developing asparaginase hypersensitivity compared to non-carriers [P=4.56×10−5; OR=2.86 (1.73–4.75) and P=1.85×10−4; OR=2.99 (1.68–5.31); n=359, respectively]. After haplotype reconstruction, the HLA-DRB1*07:01-HLA-DQB1*02:02 haplotype was associated with an increased risk. After inferring the HLA-DQA1 alleles the HLA-DRB1*07:01–HLA-DQA1*02:01–HLA-DQB1*02:02 haplotype was associated with the highest risk of asparaginase hypersensitivity [P=1.22×10−5; OR=5.00 (2.43–10.29); n=257]. Significantly fewer T-cell ALL patients carried the HLA-DQB1*02:02 allele and the associated haplotype than did pre-B-cell ALL patients (6.5%; vs. 19.2%, respectively; P=0.047). In conclusion, we identified a haplotype in the Human Leukocyte Antigen Class II region associated with a higher risk of asparaginase hypersensitivity. Our results confirm that variations in HLA-D region might influence the development of asparaginase hypersensitivity.